Lelaki Lembut: Faktor dan Kesannya kepada Pembentukan Sahsiah Mahasiswa. - Mohd Yusof, Farawahida; Timmiati, Sharifah Munirah (Sains Humanika, 2011)
This survey is conducted in order to know the factors that influence the Metro man at UTM. Besides, this research aimsto know the formation of this Metro man and to explain the position of this Metro man in the perspective of Islam. The result shows that friends seems to be the main factor that influence this Metro man besides family and media factor that can also influence them. In the Islamic context, there is no such term for Metro man. This group is categorized as transvestite and it is forbidden in Islam trying to act as a woman and undergo gender changing. At the end of the study, some ideas are proposed to certain parties in order to overcome this Metro man group.